Accurate outcome prediction after neo-adjuvant radio-chemotherapy for rectal cancer based on a TCP-based early regression index. (November 2019) - Fiorino, Claudio; Passoni, Paolo; Palmisano, Anna; Gumina, Calogero; Cattaneo, Giovanni M.; Broggi, Sara; Di Chiara, Alessandra; Esposito, Antonio; Mori, Martina; Ronzoni, Monica; Rosati, Riccardo; Slim, Najla; et al.
Highlights: A TCP-based early regression index (ERITCP ) was previously introduced. ERITCP was associated to improved survival after neo-adjuvant therapy for rectal cancer. Distant-metastasis-free survival was predicted by ERITCP and 5-FU dose. The resulting AUC (0.86) was significantly higher than models not including T ERITCP . ERITCP is a promising tool for therapy personalization. Abstract: Background and purpose: An early tumor regression index (ERITCP ) was previously introduced and found to predict pathological response after neo-adjuvant radio-chemotherapy of rectal cancer. ERITCP was tested as a potential biomarker in predicting long-term disease-free survival. Materials and methods: Data of 65 patients treated with an early regression-guided adaptive boosting technique (ART) were available. Overall, loco-regional relapse-free and distant metastasis-free survival (OS, LRFS, DMFS) were considered. Patients received 41.4 Gy in 18 fractions (2.3 Gy/fr), including ART concomitant boost on the residual GTV during the last 6 fractions (3 Gy/fr, Dmean : 45.6 Gy). Chemotherapy included oxaliplatin and 5-fluorouracil (5-FU). T2-weighted MRI taken before (MRIpre ) and at half therapy (MRIhalf ) were available and GTVs were contoured (Vpre, Vhalf ). The parameter ERITCP  = −ln[(1 − (Vhalf /Vpre )) Vpre ] was calculated for all patients. Cox regression models were assessed considering several clinical and histological variables. Cox models not including/including ERITCP (CONV_model and REGR_model respectively) were assessed and their discriminative power compared. Results: At a median follow-up of 47 months, OS, LRFS and DMFS were 94%, 95% and 78%. Due to too few events, multivariable analyses focused on DMFS: the resulting CONV_model included pathological complete remission or clinical complete remission followed by surgery refusal (HR: 0.15, p = 0.07) and 5-FU dose >90% (HR: 0.29, p = 0.03) as best predictors, with AUC = 0.75. REGR_model included ERITCP (HR: 1.019, p < 0.0001) and 5-FU dose >90% (HR: 0.18, p = 0.005); AUC was 0.86, significantly higher than CONV_model (p = 0.05). Stratifying patients according to the best cut-off value for ERITCP and to 5-FU dose (> vs <90%) resulted in 47-month DMFS equal to 100%/69%/0% for patients with two/one/zero positive factors respectively (p = 0.0002). ERITCP was also the only variable significantly associated to OS (p = 0.01) and LRFS (p = 0.03). Conclusion: ERITCP predicts long-term DMFS after radio-chemotherapy for rectal cancer: an independent impact of the 5-FU dose was also found. This result represents a first step toward application of ERITCP in treatment personalization: additional confirmation on independent cohorts is warranted.